Forms over fields and Witt's lemma - Sprehn, David; Wahl, Nathalie (MATHEMATICA SCANDINAVICA, 2020)
We give an overview of the general framework of forms of Bak, Tits and Wall, when restricting to vector spaces over fields, and describe its relationship to the classical notions of Hermitian, alternating and quadratic forms. We then prove a version of Witt's lemma in this context, showing in particular that the action of the group of isometries of a space equipped with a form is transitive on isometric subspaces.